Talent Sustainability Practices in Indonesian Financial Institutions: A Qualitative Study of Skills for Green and Inclusive Finance - Ilham Ilham; Indri Septiani; Suhendra Suhendra (Annals of Human Resource Management Research, 2026)
Purpose: This study explores how Indonesian financial institutions develop and sustain talent for green and inclusive finance, focusing on Environmental, Social, and Governance (ESG) principles. Research Methodology: A qualitative multi-case study design was employed, with data gathered through in-depth interviews with 22 professionals from banks, multi-finance firms, insurance companies, and fintech institutions. We also analyzed sustainability reports and regulatory guidelines. Thematic analysis was used to derive the insights. Results: Three main findings emerged: (1) talent sustainability is viewed as a strategic agenda, focusing on continuous skill evolution and ESG-oriented leadership; (2) competencies such as ESG risk assessment, green taxonomy literacy, and cross-functional collaboration are increasingly prioritized; and (3) HR practices are integrating ESG frameworks through structured learning pathways and performance management, despite challenges. Conclusions: Talent sustainability is crucial for the implementation of sustainable finance in Indonesia. Financial institutions that embed ESG competencies into their Human Resources) HR frameworks will be better positioned to meet regulatory demands and gain a competitive edge in the green economy. Limitations: This study is limited to financial institutions in Indonesia, and its findings may not be applicable to other sectors or countries. The qualitative design may also limit its generalizability. Contribution: This study contributes to the sustainable finance literature by linking talent sustainability with green finance practices. It offers a model for developing green finance competencies and provides practical implications for HR and future research.